PETA PEMIKIRAN PENDIDIKAN ISLAM DI INDONESIA: Telaah Dikotomi Pendidikan - Taufik, Taufik (Hunafa: Jurnal Studia Islamika, 2010)
The development ofÂ  todayâseducationÂ inÂ IndonesiaÂ Â cannot be separated from the Â influence ofÂ  the Â ideas of western state and Â those of the Islamic state. The influence brings about theÂ dichotomy ofÂ  IslamicÂ educationÂ andÂ general education, andÂ the various ideas on theÂ  purposes ofÂ education based on religion, politics, and area. Both the Islamic educationÂ  institution and general education institution have their own objective of education. The infect is that there will be some intellectuals having no good morals.Â ToÂ minimize theÂ dichotomy of Â education Â in Indonesia,Â there must be restorationÂ  of Â IslamicÂ education systemÂ and public education.Kata Kunci: pendidikan Islam, pendidikan umum, dikotomi pendidikan